NON-CANONICAL REFERENCE IN NEW TESTAMENT WRITINGS: A CASE STUDY OF JUDE 9 - Yong, Steven (Jurnal Abdiel: Khazanah Pemikiran Teologi, Pendidikan Agama Kristen dan Musik Gereja, 2025)
This paper investigates the use of non-canonical references in New Testament writings. Although the 27 books from Matthew to Revelation are widely accepted as authoritative and canonical, the epistle of Jude includes quotations from non-canonical sources, specifically the Apocryphal Book of Enoch and the Assumption of Moses. This raises important questions about the integration of non-canonical texts within canonical scripture. Through a literary analysis approach, this study examines the background of the quotation in Jude 9 from the Assumption of Moses, explores the debates surrounding this apocryphal text, and assesses the implications of incorporating non-canonical works into canonical texts. The paper aims to determine whether Jude’s authoritative status is affected by its use of such sources and to reevaluate the criteria for canonical acceptance in light of these practices.